Peran guru kelas dalam mengatasi kesulitan belajar anak slow learner di SD Muhammadiyah Dadapan - Handayani, Tri; Martaningsih, Sri Tutur (Jurnal Fundadikdas (Fundamental Pendidikan Dasar), 2022)
Inclusive schools can provide opportunities for children with special needs such as children who have slow learner learning difficulties to be able to obtain the same education in regular schools and with the existence of inclusive schools can create unity without discriminating against children's physical and academic potential. This research was conducted with the aim of describing the role of class teacher in overcoming the learning difficulties of slow learner students in SD Muhammadiyah Dadapan. The type of research used by researchers to conduct this research is qualitative research with an ethnographic approach. The subjects in this study were the principal, teachers in grades 3B and 5B, slow learner children in grades 3B and 5B. Data collection techniques used three techniques, namely interviews, observation and documentation. The validity of the data in this study used a source triangulation technique. The data analysis technique uses data collection, data reduction, data presentation and conclusions. The results of this study conclude: there are four roles that are carried out by classroom teachers for the implementation of the teaching and learning process, namely the teacher's role as a demonstrator, class manager, mediator and facilitator and evaluator, these four roles are closely related to obtaining optimal learning. Difficulties experienced by teachers in the learning process are often slow learner children who are left behind in receiving material and have difficulty distinguishing subjects, low child concentration, difficulty communicating, difficulty working on questions or being slow in collecting assignments.